Effects of geometrically cubical shaped aggregate on the engineering properties of porous asphalt - Hamzah, M.O.; S.S., Lo; Z., You; Mohd Hasan, M.R.; Abdullah, N.H. (Universiti Kebangsaan Malaysia, 2014)
Porous asphalt (PA) is predominantly made up of coarse aggregates. The coarse aggregate is instrumental in providing the strength and stability of the mix. The aggregate properties including shape is expected to greatly influence the performance of PA. In this study, five different proportions of geometrically cubical shaped (GCS) aggregate and normal shape aggregate combinations were introduced and designated as mix M0, M25, M50, M75 and M100. Further laboratory tests were carried out to determine the properties of PA including air voids, coefficient of permeability, abrasion loss, indirect tensile strength, resilient modulus and resistance to permanent deformation. The results obtained showed that mix M100 which consists of 100% GCS aggregate performed the best in all tests. Statistical analyses of one-way ANOVA and Duncan’s Post Hoc test results showed that the introduction of GCS aggregate has a significant effect on air voids, coefficient of permeability, abrasion loss and resistance to permanent deformation of the mixes. However, the results showed that GCS aggregate do not gave significant effect on indirect tensile strength and resilient modulus of the PA mixes tested.